Offshoring and the Decline of Unions - Jakob R. Munch; William W. Olney (Institute of Labor Economics (IZA), 2024)
The prevalence of labor unions have declined post-WWII, and this paper examines whether globalization is a contributing factor. Offshoring jobs abroad may change the composition of domestic firms and employment and thus reduce union density. Alternatively, a firms' ability to offshore may erode the union's bargaining power, decrease the benefits of union membership, and reduce unionization rates. We test these predictions using an employer-employee matched data set covering the universe of workers and firms in Denmark (1999-2017), which allows us to measure the exogenous threat of offshoring at the firm-level and the unionization decisions of individual workers. The findings show that the threat of offshoring reduces unionization rates, even within a job-spell. This is not driven by the changing composition of firms or workers, but instead appears to be due to a decline in the union's bargaining position. Additional results confirm that the union wage premium and the rent-sharing elasticity are both smaller at offshoring firms. These results have important policy implications for the distributional effects of globalization and for the future of organized labor.
Keywords: F66; F16; J50; 330; offshoring; unions; trade; globalization; collective bargaining